Intensification of Energy Production in the Anaerobic Digestion Process of Sewage Sludge Using Enzymatic Disintegration - Bartłomiej Macherzyński; Elżbieta Popowska-Nowak; Maria Włodarczyk-Makuła; Beata Bień; Małgorzata Wszelaka-Rylik (Energies, 2024)
This paper presents results of a study on changes in the physical and chemical properties of papain-disintegrated sewage sludge subjected to methane fermentation and the effect of enzymes on the colony number of Escherichia coli, Salmonella spp. and Legionella spp. Fermentation studies were conducted in five batches, in which papain was introduced in amounts representing 0, 1, 2, 3 and 4% (w/w) by weight of the sludge dry matter content. The use of enzymatic disintegration allowed us to intensify the decomposition of organic compounds in the digestion process up to 31% and increase biogas production up to 41% compared to control sludge. At the same time, an almost complete reduction (99–100%) in the colony number of E. coli and Salmonella spp. could be achieved. Therefore, enzymatic disintegration can be competitive with physical or chemical disintegration methods.